Assessment of crack growth development in main pipeline on the basis of elastoplastic model - К. А. Vansovich; I. P. Aistov; А. А. Nakhlestkin; D. S. Beseliya (Омский научный вестник)
A method for predicting the growth of surface cracks in the wall of the main pipeline under action of operational loads is proposed. The elastoplastic model of surface crack growth under biaxial loading is described on the example of steel 20. ANSYS developed an algorithm for modeling crack growth taking into account residual stresses. The forms and sizes of crack opening under varying loading cycles of the pipeline are determined. The dependence of the crack growth rate under varying loads on the stress state in front of the crack tip is established. The influence of overload cycles on crack growth is investigated. The technique of crack development prediction based on in-line diagnostics and pipeline loading monitoring is described.